Enhancement of Mechanical Properties and Testing of Nitinol Stents in Cerebral Aneurysm Simulation Models. Issue 12 (29th September 2015) - Nam, Hyo Geun; Yoo, Chang Min; Baek, Seoung Min; Kim, Han Ki; Shin, Jae Hee; Hwang, Min Ho; Jo, Ga Eun; Kim, Kyong Soo; Cho, Jae Hwa; Lee, Seung Hoon; Kim, Ho Chul; Lim, Chun Hak; et al.
Abstract: Stents are promising medical devices widely used in the prevention of cerebral aneurysm rupture. As the performance of stents depends on their mechanical properties and cell configuration, the aim of this study was to optimize the stent design and test the hemodynamic properties by using computational solid mechanics and computational fluid dynamics. In order to test their performance, computer‐based cerebral aneurysm models that mimic the conditions present after implantation into the human brain were tested. The strut configuration selected was the closed‐cell type, and nitinol was chosen as the material for stent manufacture because the innate characteristics of this material increase stent flexibility. Three ideal sample stent types with different cell configurations were manufactured. Computational solid mechanics analysis of the sample stents showed over 30% difference in flexibility between stents. Furthermore, using a cerebral aneurysm model simulation, we found that the stents eased the hemodynamic factors of the cerebral aneurysm and lessened the flow velocity influx into the sac. A decrease in flow velocity led to a 50–60% reduction in wall shear stress, which is expected to prevent aneurysm rupture under clinical conditions. Stent design optimization was carried out by simulation and electropolishing. Corrosion resistance and surface roughness were evaluated after electropolishing performed under variable conditions, but 40 V and 10 s were the most optimal.